Characterizing rainfall in the south‐western Cape, South Africa: 1841–2016. (8th November 2019) - Ndebele, Nothabo E.; Grab, Stefan; Turasie, Alemtsehai
Abstract: The rainfall series from the South African Astronomical Observatory in Cape Town, South Africa, is one of the longest known single site instrumental records in the southern hemisphere, spanning over 176 years. Rainfall data are analysed to determine trends and periodicity in the series for annual, seasonal and monthly time scales. Using the Mann Kendall test and Sen's slope, significant negative rainfall trends are recorded for the months of March and October, and for the spring season (from September to November). Using the Mann Kendall and its modified versions to account for serial correlation, as well as a multi‐temporal trend analysis, we demonstrate a positive rainfall trend during the first 60 years (i.e., 1841–1900), which thereafter changes to a long‐term (1900–2016) negative trend, but incorporating a shorter 40 years significant positive trend between 1930 and 1970. We identify cyclic patterns with recorded periods of 9–12 years, 16–30 years and 30–42 years for rainfall, the Southern annular mode (SAM) and Southern oscillation index (SOI). In addition to the notable 9–12 years rainfall cycle that is evidently associated with sunspot cycles, 20–30 years and longer 32–40 years rainfall, solar, SAM and SOI cycles are also identified. Abstract : A study of long‐term rainfall in the southwestern Cape which explores trends over short and long periods during 1841–2016 and cyclic rainfall patterns associated with the Southern annular mode, Southern oscillation index and solar activity.